Clinical outcomes of robot-assisted radical cystectomy and continent urinary diversion. (4th May 2019) - Hosseini, Abolfazl; Ebbing, Jan; Collins, Justin
Abstract: Robot-assisted radical cystectomy (RARC) with intracorporeal orthotopic neobladder (ONB) can be recognized to be the supreme discipline in urological pelvic surgery. The utilization of RARC with intracorporeal urinary diversion (ICUD) has increased during the last 15 years. This increase is primarily noted for ICUD with ileal conduits, but with a lesser extent also for IC neobladders, with an increase from 7% in 2005 to 17% in 2016. However, these observations are limited to a few centers of excellence reflecting the fact that IC ONB formation is regarded as technically challenging and time-consuming with a steep learning curve. The objective of this review is to summarize the current data about RARC with IC ileal ONB in terms of patient selection, preoperative preparation, functional outcomes, complications and oncological outcomes. Careful patient selection considering absolute and relative contraindications for RARC and/or ONB as well as the implementation of an enhanced recovery after surgery protocol is an integral part of successful oncological, functional and complication outcomes. Nerve sparing procedures in males and gynaecological organ sparing in females should be attempted in order to maximize functional outcomes. Different techniques of ICUD with ONB after RARC are described; however, all of them adhere to the principles for the functioning of an ONB. Both functional outcomes and complication rates have been improved significantly during the last few years. The current evidence for long-term outcomes following RARC shows acceptable oncological outcomes comparable to an open series including recurrence-free survival data, positive surgical margin rates and median pelvic lymph node yields.